2019
DOI: 10.1016/j.ijnurstu.2019.103414
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nursing students' competence in clinical practice: A systematic review of reviews

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 41 publications
1
86
0
3
Order By: Relevance
“…Regular mentoring by a nurse teacher can improve the student's clinical experience and simultaneously ensure that they achieve their learning outcomes. From a student's point of view, the mentoring nurse teacher should be present and available at regular intervals (Price et al, 2011;Pitkänen et al, 2018), starting at the beginning of clinical practice and continuing until the final evaluation (Immonen et al, 2019). This study revealed that certain students desire mentoring before the start of clinical practice to get an introduction to the upcoming clinical practice.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Regular mentoring by a nurse teacher can improve the student's clinical experience and simultaneously ensure that they achieve their learning outcomes. From a student's point of view, the mentoring nurse teacher should be present and available at regular intervals (Price et al, 2011;Pitkänen et al, 2018), starting at the beginning of clinical practice and continuing until the final evaluation (Immonen et al, 2019). This study revealed that certain students desire mentoring before the start of clinical practice to get an introduction to the upcoming clinical practice.…”
Section: Discussionmentioning
confidence: 91%
“…In order to succeed in learning and future professional development, nursing students need good preparation for clinical placement, which includes setting their own learning outcomes, taking accountability for their own learning and the development of an interest in the profession, and commitment towards learning (Jokelainen, 2013). In the latest review of reviews (Immonen et al, 2019) relating to clinical assessment of nursing students' clinical practice, it was found that the focus of assessment needs to be on students' continuous learning instead of their final evaluation and grading, with reflection and constructive feedback from the clinical mentor and nurse teacher.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, students recently surveyed by Pitkänen et al (2018) believed that aspects of the mentoring relationship including frequent unscheduled discussions with their mentors and planning their learning outcomes enhanced their learning. In addition, a systematic review by Immonen et al (2019) found evidence of a direct connection between clear mentoring practice in a healthcare organization and guidance of students' learning processes (including goalorientation, reflection, constructive feedback and student-centred evaluation). These findings suggest that, by promoting a positive circle of mentors' competences, it is possible to enhance a student-centered evaluation as a main outcome to improve students' clinical learning experiences.…”
Section: Introductionmentioning
confidence: 99%
“…While most of the clinical instructors are fair and just, considerate, and patient, some participants noted some inaccuracies hence the need to revisit practices in student learning assessment as an essential component of the clinical instructorship. Immonen et al (2019) identified the best current evidence on the assessment of nursing students' competence in clinical practice. According to them, the development of more consistent and systematic approaches in assessment with high reliability and validity is much desired and needed (Immonen at al., 2019).…”
Section: Limits and Discussionmentioning
confidence: 99%
“…Immonen et al (2019) identified the best current evidence on the assessment of nursing students' competence in clinical practice. According to them, the development of more consistent and systematic approaches in assessment with high reliability and validity is much desired and needed (Immonen at al., 2019). Provisions to have clear assessment criteria, nurse educators' support, reinforcement about assessment, enhanced feedback practices, and opportunities for reflection among students (Immonen et al, 2019) are crucial.…”
Section: Limits and Discussionmentioning
confidence: 99%